Methodology used by field hockey coaches in Spain - Ibáñez de la Rosa, JC.; Giménez Fuentes-Guerra, FJ.; Abad-Robles, MT.; Robles-Rodríguez, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The objective of this research has been to know the methodology used by grass-room hockey coaches throughout the national territory. A total of 172 coaches from all over Spain, (57 women, 33.10% and 115 men, 66.90%), divided into 9 Autonomous Communities through a questionnaire were studied. The most relevant results showed that hockey coaches use both managerial and discovery teaching methods. Also, technical-tactical means are prioritized with respect to physical aspects, and the game is present in all sessions. The coaches consider, to a greater extent than the coaches, that the competition in these ages is adapted to the psychoevolutive characteristics of the players (p = 0.039). On the contrary, they are more in agreement with the fact of maintaining cordial relations with the parents of their players (p = 0.025).